William Woys Weaver: Sauerkraut Yankees. Pennsylvania Dutch Foods and Foodways - Davidson, Alan (Petits Propos Culinaires, 2024)
William Woys Weaver: Sauerkraut Yankees. Pennsylvania Dutch Foods and Foodways – second edition: Stackpole Books, Mechanicsburg PA, 2002: ISBN 0-8117-151-0: 216 pp., b/w illus., h/b, 19.95.